Chemical removal in waste stabilisation pond systems of varying configuration - Linge, Kathryn; Liew, Deborah; Gruchlik, Yolanta; Busetti, Francesco; Ryan, Una; Joll, Cynthia (ROYAL SOC CHEMISTRY, 2021)
While nutrient removal has been well studied in waste stabilisation ponds (WSPs), studies of organic micropollutant removal in pond systems are limited. In this study, we investigated organic micropollutant, nitrogen and organic carbon removal in selected WSPs that differed in geographical location and pond configuration, and compared their performance to an oxidation ditch wastewater treatment plant (WWTP). Of the 232 chemicals measured, 36 were detected in wastewater influent and 33 were detected in treated wastewater effluent. New data for micropollutant removal in WSPs was generated for three pesticides or related chemicals, five pharmaceuticals, the plasticizer N-butylbenzenesulfonamide, the antioxidant 2,6-di-t-butyl-p-cresol, and two flame retardants tris(dichloropropyl)phosphate and tris(chloropropyl)phosphate isomers. Most of these micropollutants were relatively well removed in WSPs. The poorest treatment efficiency was observed in the single facultative pond system, with no maturation pond, suggesting that the presence of a maturation pond is important for chemical removal. The two WSPs in temperate climates were found to have higher concentrations of motile algae that can optimise their position with respect to light and temperature. However, to-date, the micropollutant removal by these algal species is not known. The highest removals of micropollutants in a WSP were measured in a complex WSP system with two maturation ponds, and the removals achieved were comparable to the oxidation ditch system. The key factors contributing to high micropollutant removal in this WSP were high solar irradiation and warm temperatures that promoted the growth of non-motile green algae previously found to degrade micropollutants, and photodegradation.